Research on the Anti-inflammatory Cooling Effect of Marine Fish Oil ω-3 Microencapsulated Foam Layers in Sports Knee Pads - Zhu, Lingjun (International Journal of Humanities and Social Science, 2026)
This research investigates the anti-inflammatory and cooling effects of marine fish oil ω-3 microencapsulated foam layers integrated into sports knee pads. Inflammation and overheating are common issues during sports activities, leading to discomfort and potential injuries. Marine fish oil ω-3 fatty acids are known for their anti-inflammatory properties, and microencapsulation enhances their stability and controlled release. We hypothesize that incorporating microencapsulated ω-3 into foam layers of knee pads will reduce inflammation and provide a cooling effect, thereby improving athletic performance and recovery. The study involves synthesizing ω-3 microcapsules, fabricating foam layers with varying concentrations of these microcapsules, and characterizing their physical and chemical properties. In vitro release studies will assess the release kinetics of ω-3 fatty acids from the foam. In vivo experiments will evaluate the anti-inflammatory and cooling effects of the knee pads on athletes during exercise, using measures such as skin temperature, inflammatory markers in blood samples (e.g., TNF-α, IL-6), and subjective comfort scales. A control group wearing standard knee pads will be compared. The findings will provide valuable insights into the potential of ω-3 microencapsulated foam for sports applications and contribute to the development of advanced wearable technologies for sports and healthcare.